JISIoT 2020
DOI: 10.54216/jisiot.020102
|View full text |Cite
|
Sign up to set email alerts
|

ERP Implementation Road Map for Small and Medium Size Enterprises (SMEs)

Abstract: The definitions of small and medium enterprises (SMEs) vary from country to country and industry to industry, each country or region has their own definition which depends on who defines it and where is utilized. SMEs play an essential role in most economies, particularly in developing countries. Many large enterprises depend on SMEs (Startups) for their supply chain; thus, SMEs need to adopt Enterprise Resources Planning (ERP) systems more and more. Since ERP system adoption is a challenging project in SMEs, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…Creatures in the Earth's ecological cycle predate human beings' possible existence. Our uncontrolled and excessive consumption of the Earth's resources has caused irreparable damage to the space environment in which they live [ 16 , 17 ]. It is not fair to them.…”
Section: Methods Of Green Innovation and Enterprise Sustainable Devel...mentioning
confidence: 99%
“…Creatures in the Earth's ecological cycle predate human beings' possible existence. Our uncontrolled and excessive consumption of the Earth's resources has caused irreparable damage to the space environment in which they live [ 16 , 17 ]. It is not fair to them.…”
Section: Methods Of Green Innovation and Enterprise Sustainable Devel...mentioning
confidence: 99%
“…Establishing a big data benefit model of green supply chain finance and using the replication dynamic equation method to study the impact of big data sustainability, provides an effective way to promote small and medium-sized enterprises in the upstream supply chain to use environmental management strategies to carry out production [ 23 ]. In this paper, the green degree improvement X of the entire supply chain is taken as the research variable.…”
Section: Big Data Benefit Model Of Green Supply Chain Financementioning
confidence: 99%
“…Efe [17] uses both the integration of fuzzy AHP (Analytic Hierarchy Process) and fuzzy TOPSIS (a technique to order preference using similarity to ideal solution) and a hydride module between both fuzzy AHP and fuzzy TOPSIS applying different decision-makers as recommended; the proposed methodology decreases the uncertainty with a group of decision-makers. Zaied and Mohmed [18] represent a road map for implementing ERP systems in small and medium enterprises (SMEs) showing the effect on the world economy and the benefit gained from applying ERP solutions in SMEs. Additionally, it shows the steps and guides to implement an ERP system in SMEs, which are considered a part not only of the success and failure of implementing the ERP but also of the research explaining the ERP selection criteria for the SMEs; different researchers' methods concluded that implementing the ERP in SMEs depends on their readiness assessment, which mainly includes team and infrastructure and involves proposing guidance to follow the assessment and make a decision.…”
Section: Methodologies For Selecting Erp Systemsmentioning
confidence: 99%